Controlling Nucleation and Growth of Metal Halide Perovskite Thin Films for High‐Efficiency Perovskite Solar Cells. Issue 14 (2nd February 2017) - Sakai, Nobuya; Wang, Zhiping; Burlakov, Victor M.; Lim, Jongchul; McMeekin, David; Pathak, Sandeep; Snaith, Henry J.
Abstract : Metal halide perovskite thin films can be crystallized via a broad range of solution‐based routes. However, the quality of the final films is strongly dependent upon small changes in solution composition and processing parameters. Here, this study demonstrates that a fractional substitution of PbCl2 with PbI2 in the 3CH3 NH3 I:PbCl2 mixed‐halide starting solution has a profound influence upon the ensuing thin‐film crystallization. The presence of PbI2 in the precursor induces a uniform distribution of regular quadrilateral‐shaped CH3 NH3 PbI3 perovskite crystals in as‐cast films, which subsequently grow to form pinhole‐free perovskite films with highly crystalline domains. With this new formulation of 3CH3 NH3 I:0.98PbCl2 :0.02PbI2, this study achieves a 19.1% current–voltage measured power conversion efficiency and a 17.2% stabilized power output in regular planar heterojunction solar cells. Abstract : A fractional substitution of PbI2 in the mixed‐halide precursor (3MAI:PbCl2 ) has a profound impact upon the crystallization process and on the as crystallized film morphology and electronic properties. The "structurally improved" film delivers a J–V measured power conversion efficiency of 19.1%.